2019
DOI: 10.1038/s41598-019-50702-2
|View full text |Cite
|
Sign up to set email alerts
|

A cryptic hydrophobic pocket in the polo-box domain of the polo-like kinase PLK1 regulates substrate recognition and mitotic chromosome segregation

Abstract: The human polo-like kinase PLK1 coordinates mitotic chromosome segregation by phosphorylating multiple chromatin- and kinetochore-binding proteins. How PLK1 activity is directed to specific substrates via phosphopeptide recognition by its carboxyl-terminal polo-box domain (PBD) is poorly understood. Here, we combine molecular, structural and chemical biology to identify a determinant for PLK1 substrate recognition that is essential for proper chromosome segregation. We show that mutations ablating an evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…Therefore, we propose that the conserved hydrophobic amino acids within the MADBUB PBM act to stabilize PLK1 binding, and perhaps additionally to allow PLK1 dimerization and activation at kinetochores. In support of this idea, targeting the hydrophobic pocket on PLK1 directly, using mutations or small molecule inhibition, causes reduced PLK1 recruitment to kinetochores and a mitotic arrest associated with misaligned chromosomes ( Sharma et al, 2019 ). We hypothesize that impaired interaction of PLK1 with the BUB complex is at least partially responsible for these phenotypes.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, we propose that the conserved hydrophobic amino acids within the MADBUB PBM act to stabilize PLK1 binding, and perhaps additionally to allow PLK1 dimerization and activation at kinetochores. In support of this idea, targeting the hydrophobic pocket on PLK1 directly, using mutations or small molecule inhibition, causes reduced PLK1 recruitment to kinetochores and a mitotic arrest associated with misaligned chromosomes ( Sharma et al, 2019 ). We hypothesize that impaired interaction of PLK1 with the BUB complex is at least partially responsible for these phenotypes.…”
Section: Resultsmentioning
confidence: 97%
“…A final striking feature of the core PBM is the conserved stretch of hydrophobic residues before and immediately after the Ser-Thr-Pro motif. PLK1 has recently been shown to use a conserved hydrophobic pocket that lies adjacent to the phospho-substrate binding groove to enhance substrate binding affinity ( Sharma et al, 2019 ). Although this pocket is often found in a closed conformation, it also exhibits a variety of crystal packing interactions with hydrophobic residues, demonstrating a high degree of flexibility ( Śledź et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…A number of non-catalytic pockets were also found that are targeted by weak ligands that may be valid starting points for the development of ProxPharm compounds (Table S1, confidence level 2). These include compounds and peptides found in the POLO-box domain of PLK1 (Figure 4) 29 and the PDZ domain of PTPN3 (Figure 6) 42 . Less reliable, but still promising are domains for which no ligand was reported in the context of the protein of interest, but that were shown to be chemically tractable in other proteins (confidence level 3).…”
Section: Discussionmentioning
confidence: 99%
“…However, the PBD confer specificity among the PLK family suggesting little redundancy in their functionality [ 66 ]. A recent report inferred the contribution of an additional tyrosine-rich pocket close to the phospho-peptide binding pocket to their substrate specificity [ 67 ].…”
Section: The Writers — Slim-based Interactions That Target Kinases To Their Substratesmentioning
confidence: 99%